ALCOHOL IN DRIVERS FATALLY INJURED IN ROAD ACCIDENTS IN ALBANIA DURING THE YEARS 2010-2012 - Matua, Linda; Cinije, Mirnela; Petrela, Elizana; Jucja, Besnik (European Scientific Journal, ESJ, 2013)
Aim: To assess the presence of alcohol among Albanian drivers involved in fatal road accidents between 2010 and 2012. Materials and methods: Samples were obtained for 365 drivers involved in road accidents from January 2010 to December 2012. Blood samples have been analyzed foe the presence of ethanol by GC –HS (Gas-Chromatograph Head Space) in the Laboratory of Forensic Toxicology in the Institute of Forensic Medicine in Tirana which is the only authorized institution to perform the toxicological investigation of road accidents that happen in Albania. Results: In the final cohort of 365 persons involved in traffic accidents, alcohol were found in concentrations above the legal limit in samples from 45.2% of subjects. BAC exceeded 0.50 g/l mostly in male subjects (98.8%). There were involved in traffic crashes mostly, car drivers (57.9%) and pedestrian (29.1%), consisting 41.9% of fatally cases each group. Conclusion: Males have the chance to crash 18% more than females. [OD: 1.18; CI95%: 1.01-7.76]. Blood alcohol concentrations (0.2 g/l ≥BAC≤ 0.5 g/l) are not an influence factor in fatal road accidents. Subjects whose blood alcohol concentrations have a alcohol blood level equal to (0.5 g/l ≥BAC≤ 1 g/l) have the chance to be involved in a fatal accident 2.2 times more then subjects whose blood alcohol concentration is below 0.2 g/l [OD = 2.2 ; CI 95%; 1.09-4.55]. Subjects with a blood alcohol concentration over > 1 g/l, have the chance to be involved in a fatal accident approximately two times more than a subject with a BAC <0.2g/l. [OD 1,98; CI 95%; (1.23-3.02)].